Una lectura del «Llibre de Meravelles» como "ars praedicandi" - Domínguez Reboiras, Fernando (Caplletra. Revista Internacional de Filologia, 2007)
The «Llibre de meravelles» is one of the best known works by Ramon Llull because of its literary dimension. Both this and the structure of the text correlate with contemporary texts of encyclopaedic character. However, a contextualization of the book within Llull’s production, especially in relation to his former novel (Blanquerna), canmake important contributions to a new approach to the book, in order to interpret it as a manual of predication adapted to Llull’s particular conception. Which his conception is, which purpose Felix’s examples have in the book, and how the work integrates in Llull’s conception of relationships between faith and reason, is the subjectof the present article.